Міжгрупові розколи в об’єднаних територіальних громадах: ризики послаблення соціальної згуртованості в децентралізованій Україні - Дейнеко, Олександра; Deineko, Оleksandra (Волинський національний університет імені Лесі Українки, 2020)
У статті здійснено аналіз міжгрупових розколів у сприйнятті мешканців об’єднаних територіальних громад Харківської та Чернівецької областей як потенційного чинника послаблення соціальної згуртованості на рівні локальних спільнот в Україні. Спираючись на модель емпіричного вимірювання соціальної згуртованості Дж. Чана, ми здійснюємо спробу її адаптації в контексті якісної соціологічної перспективи, аналізуючи дані 26 напівструктурова-них інтерв’ю, проведених із місцевими громадськими активістами, депутатами місцевих рад, представниками адміністрації об’єднаних громад й експертами з питань децентралізації в обох регіонах України. Дослідження засвідчило наявність міжгрупових розколів за осями «новостворена громада – попередня влада»; «влада громади – місцеві мешканці»; «центр – периферія»; «багаті громади – бідні громади»; «децентралізована Україна – недецентралізована Україна». Ключовим підґрунтям для формування розколів визначено соціальні нерівності, що зумовлюють «метаморфози спроможності» реформи децентралізації в Україні. Наголошено на актуальності початку адміністративного етапу реформи децентралізації, що сприятиме скороченню соціального розриву між децентралізованою та недецентралізованою Україною. The paper is dedicated to studying major inter-group cleavages in amalgamated territorial hromadas in Ukraine as a horizontal objective component of social cohesion weakening proposed by J. Chan. The author has realized the attempt to adapt Chan’s model of social cohesion measurement in the framework of qualitative sociological perspective, basing on analysis of 26 semi-structured interviews conducted with decentralization experts, representatives of civil society, local elected officials and local authorities in the amalgamated hromadas two border regions of Ukraine – Kharkiv and Chernivtsi. The study has shown the existence of such types of inter-group cleavages «newly established hromada – the previous local authorities»; «hromada authorities – locals»; «сenter-periphery»; «rich hromadas - poor hromadas»; «decentralized Ukraine - non-decentralized Ukraine». Existence of social expectations of «old» corrupt practices reproduction in the management of the newly amalgamated hromadas, which destroys the notion of decentralization as a mechanism of strengthening democracy and transparency is identified in the study as well as the risks of local elites capture. The research has shown that various starting points of territorial units in readiness to implement the reform, the voluntary nature of amalgamation and the weak control of the implementation contributed to the formation of new intergroup alliances on the principle of «rich with rich», that led to both deepening social inequality in Ukraine and strengthening of closed «social orders» establishing. The author has emphasized the urgency of the beginning of decentralization reform administrative stage, which helps to reduce the social gap between decentralized and non-decentralized Ukraine. В статье анализируются межгрупповые расколы в восприятии жителей объединенных территориальных громад Харьковской и Черновицкой областей как потенциальный фактор ослабления социальной сплоченности на уровне локальных сообществ в Украине. Опираясь на модель эмпирического измерения социальной сплоченности Дж. Чана, делаем попытку ее адаптации в контексте качественной социологической перспективы, анализируя данные 26 полуструктурированных интервью, проведенных с местными общественными активистами, депутатами местных советов, представителями администрации объединенных громад и экспертами по вопросам децентрализации в обеих регионах Украины. Исследование показало наличие межгрупповых расколов по осям «созданная громада – предыдущая власть»; «власть громады – местные жители»; «центр – периферия»; «богатые громады – бедные громады»; «децентрализованная Украина – недецентрализованная Украина». Ключевым основанием для формирования расколов определены социальные неравенства, которые обусловливают «метаморфозы способности» реформы децентрализации в Украине. Подчеркивается актуальность начала административного этапа реформы децентрализации, способствующего сокращению социального разрыва между децентрализованной и недецентрализованной Украиной.
Inter-Group Cleavages in Amalgamated Territorial Hromadas: Risks of Social Cohesion Weakening in Decentralized Ukraine
Keywords: міжгрупові розколи; об’єднані територіальні громади; децентралізація; соціальна згуртованість; соціальна нерівність; inter-group cleavages; amalgamated territorial hromadas; decentralization; social cohesion; social inequality; 316.334.52:342.25(477)